SYNTHESIS OF 3-(2-PYRIDYL)-N-METHYL-1,2,4-TRIAZOLE-5-ACETIC ACID ETHYL ESTER AND THEIR COORDINATION COMPOUNDS WITH Pd(II): UDC 546.98+547.792+543.429.23 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
Alkylation of 3-(2-pyridyl)-1,2,4-triazole-5-acetic acid  with iodomethane leads to formation of 3-(2-pyridyl)-N1-methyl-1,2,4-triazole-5-acetic acid ethyl ester (L1) and 3-(2-pyridyl)-N2-1,2,4-triazole-5-acetic acid ethyl ester (L2). It was also managed to identify the compound ethyl ester 3-(2-pyridyl)-N2-methyl-1,2,4-triazol-5-yl-α-propionic acid (L3) which is the product of alkylation of L2 in the methylene group. L1-3 were used for synthesis of palladium(II) complexes PdL1Cl2, PdL2Cl2 and PdL3Cl2. The composition and structure of obtained compounds were proposed on the basis of IR and 1H NMR spectroscopy data and elemental analysis.IR spectra of synthesized ligands have a lot in common, due to their structure similarity. As a result of coordination all signals in the IR spectra are shifted besides bands of ester groups. 1H NMR spectra of obtained ligands is bit similar, this is due to their structure. Signals of pyridine ring protons 3-(2-pyridyl)-N1-methyl-1,2,4-trazole-5-acetic acid ethyl ester shifted to 0.11–0.13 ppm in a weak field in compare with  izomers. N1–CH3 signals are shifted to lower field than N2–CH3, it can be explained by the influence of negative magnetic anisotropy of pyridine ring. Methyl and methylene signals of ester group are located nearly in the same field in L1–3.Coordination of all ligands occurs through the nitrogen atom of pyridine ring and N4-triazole. In this case all L1, L2 and L3 signals of pyridine  protons suffer shift to a low field. Methyl and methylene signals of ester group almost no shifted what indicate that no coordination through oxygen atom.
Keywords: 1,2,4-triazole, palladium(II), IR spectroscopy, NMR spectroscopy